2018
DOI: 10.1002/slct.201802709
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐Enriched Cobalt Phosphide with Assorted Nanostructure as a Multifunctional Electrode for Energy Conversion and Storage Devices

Abstract: A single‐step hydrothermal technique is applied to prepare cobalt phosphide with multifarious nanostructures to signify its multifunctional capabilities. The prepared electrodes were intensely analysed for both the energy conversion and energy storage systems. The acquired Co−P with the assorted morphology of scaffolds and spherical of Co2P/C electrode inspires with a significantly lower oxygen evolution reaction (OER) (271 mV()η10 ) and hydrogen evolution reaction (HER) (207 mV()η10 ) overpotentials to accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Figure a displays high-resolution XPS spectra of Co 2p, where the split peaks correspond to Co 2p 3/2 and Co 2p 1/2 orbitals, respectively. The deconvolution results indicated coexistence of Co 3+ (780.1 and 796.0 eV) and Co 2+ (781.4 and 797.4 eV). , The incorporation of Fe resulted in an increased abundance of Co 3+ in Co 4 Fe 0.5 Ni 0.5 OOH-NRs (29.5 at. %) and Co 4 FeOOH-NRs (42.4 at.…”
Section: Resultsmentioning
confidence: 89%
“…Figure a displays high-resolution XPS spectra of Co 2p, where the split peaks correspond to Co 2p 3/2 and Co 2p 1/2 orbitals, respectively. The deconvolution results indicated coexistence of Co 3+ (780.1 and 796.0 eV) and Co 2+ (781.4 and 797.4 eV). , The incorporation of Fe resulted in an increased abundance of Co 3+ in Co 4 Fe 0.5 Ni 0.5 OOH-NRs (29.5 at. %) and Co 4 FeOOH-NRs (42.4 at.…”
Section: Resultsmentioning
confidence: 89%
“…In the past few decades, the research on hydrogen evolution of transition metal-based materials (such as nitrides, phosphides, sulfides and so on) has made great progress. 9,[13][14][15][16] In particular, layered transition metal dichalcogenides (TMDs) have emerged as potential alternatives to Pt-based catalysts. 9 As a representative example, MoS 2 with an appropriate ΔG H* value has been widely studied, 17,18 although its active sites are located at the layer edge.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a nitrogen-enriched graphene quantum dots (C-GQDs) catalyst was developed with an efficient electrocatalytic activity, and the charge distribution of pyridine and pyridine N-oxide is induced through the π–π delocalization process, which could encourage their OER activity [ 19 ]. Surendran et al [ 20 ] hydrothermally synthesized the spherically nanostructured carbon-enriched cobalt phosphide multi-functional electrode for water electrolyzer studies, and reported the current density of 10 mA cm −2 @ 1.63 V. Qian et al [ 21 ] prepared a cost-effective, larger specific surface area with high electrically conductive natured MWCNTs for the making of a thermo-electrochemical (TEC) catalyst by the electrochemical deposition (EPD) method. The prepared MWCNT TEC catalyst could display a high power density (45.2 A cm −2 ) with long-term cyclic stability.…”
Section: Introductionmentioning
confidence: 99%